Badania kliniczne i doświadczalne w chorobach serca, słuc i naczyń Leczenie przewlekłej pozawałowej niewydolności mięśnia serca poprzez implantację własnych jednojądrowych komórek szpikowych w region akinezy miokardium - Hendzel, Piotr; Szałański, Przemysław; Korsak, Jolanta; Budziszewska, Katarzyna; Zagrodzka, Magdalena; Gryszko, Leszek (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2007)
Background: For the past few years reconstructive medicine and work involving stem cells have been flourishing; it seems therefore natural to seek treatment of myocardial failure that aims at reconstructing the function of left ventricular wall damaged as a result of ischaemia. Aim: Demonstration of efficacy and safety of postinfarct heart failure treatment with autologous bone marrow stem-cell implantation (ABMCI), combined with off-pump coronary artery bypass (OPCAB). Material and methods: A group of 10 patients with postinfarct heart failure underwent OPCAB with autologous bone marrow mononuclear cells implanted into the akinetic region of the anterior wall. Monitoring encompassed the course of the early postoperative period, and in the mid-term and long-term course the postoperative myocardial growth and the left ventricular function in 64-row CT were observed. Results: Early. In patients between the 6th and 24th hour after surgery there was an increase in the cardiac index (mean CI prior to surgery 2.12 l/m 2 min, SD±0.48; mean CI 24 hrs after surgery 3.5 l/m 2 min SD±0.92; p=0.002, test T). Mid-term and long-term. An increment in the mean thickness of the anterior wall by 2.38 mm (SD±2.07, p=0.04, test T) was observed as well as an increase of the left ventricular ejection fraction (prior to surgery EF% mean 21.26 SD±11.88, post surgery EF% mean 29.06 SD±10.13, p=0.07, test T). Conclusions: Implantation of autologous marrow cells combined with OPCAB may be an effective method of postinfarct heart failure treatment. The implanted stem cells cause an increase in the thickness of the left ventricular wall.